Ketamine specifically reduces cognitive symptoms in depressed patients: An investigation of associated neural activation patterns. (April 2021) - Stippl, A.; Scheidegger, M.; Aust, S.; Herrera, A.; Bajbouj, M.; Gärtner, M.; Grimm, S.
Abstract: Major depressive disorder (MDD) is characterized by heterogeneous cognitive, affective and somatic symptoms. Hence, the investigation of differential treatment effects on these symptoms as well as the identification of symptom specific biomarkers might crucially contribute to the development of individualized treatment strategies. We here aimed to examine symptom specific responses to treatment with ketamine, which repeatedly demonstrated rapid antidepressant effects in severe MDD. Additionally, we investigated working memory (WM) related brain activity associated with changes in distinct symptoms in order to identify specific response predictors. In a sample of 47 MDD patients receiving a single sub-anesthetic dose of ketamine, we applied a three-factor solution of the Beck Depression Inventory (BDI) to detect symptom specific changes 24 h post-infusion. A subsample of 16 patients underwent additional fMRI scanning during an emotional working memory task prior to ketamine treatment. Since functional aberrations in the default mode network (DMN) as well as in the dorsolateral prefrontal cortex (DLPFC) have been associated with impaired cognitive and emotional processing in MDD, we investigated neural activity in these regions. Our results showed that ketamine differentially affects MDD symptoms, with the largest symptom reduction in the cognitive domain. WM related neuroimaging results indicated that a more pronounced effect of ketamine on cognitive symptoms is predicted by lower DMN deactivation and higher DLPFC activation. Findings thereby not only indicate that ketamine's antidepressant efficacy is driven by a pro-cognitive mechanism, but also suggest that this might be mediated by increased potential for adaptive adjustment in the circumscribed brain regions.